Effects of music listening on anaerobic performance and motivation in healthy young adults - Cavaggioni, Luca; Formenti, Damiano; Ouergui, Ibrahim; Perpetuini, David; Castiglioni, Paolo; Berengan, Alessandro; Trecroci, Athos; Ardigò, Luca Paolo; Merati, Giampiero (Frontiers in Sports and Active Living, 2025)
IntroductionThe study aimed to investigate and confirm from a physiological and psychological perspective whether preferred music would influence anaerobic performance during the Running-Based Anaerobic Sprint Test (RAST).MethodsA total of 18 (men, n = 12, women, n = 6) sub-élite track-and-field and football athletes (mean age 22.2 ± 2.1 years, mean height 175.3 ± 8.0 cm, mean weight 66.4 ± 10.6 kg, mean BMI 21.5 ± 2.2 kg/m2) were voluntarily recruited. The RAST procedure was performed by recording maximum power (Pmax), average power (Pmean), minimum power (Pmin), rating of perceived exertion (RPE), and motivational level (visual analog scale) while listening to preferred or no music through headphones.ResultsListening to music significantly increased motivation (p < 0.001, effect size = 1.31, very large) compared to no music. However, no significant differences were observed in other performance variables between the “with music” and “without music” conditions.ConclusionsOverall, listening to preferred music during an anaerobic exercise improves motivation as confirmed by previous evidence. This could be helpful for athletes to strive for even higher goals by improving their current performance level.